112k views
5 votes
if p(x)=x*2-1 and q(x)=5(x-1),which expression is equivalent to (p-q)(x)?

1 Answer

6 votes

Answer:


(p - q)(x) = (x -1) (x - 4)

Explanation:

Given


p(x) = x^2 - 1


q(x) = 5(x - 1)

Required

(p - q)(x)

This is represented as:


(p - q)(x) = p(x) - q(x)


(p - q)(x) = x^2 - 1 - 5(x - 1)


(p - q)(x) = x^2 - 1 - 5x + 5

Collec like terms


(p - q)(x) = x^2 - 5x + 5 - 1


(p - q)(x) = x^2 - 5x + 4

Expand


(p - q)(x) = x^2 -4x - x + 4

Factorize


(p - q)(x) = x(x -4) - 1(x - 4)


(p - q)(x) = (x -1) (x - 4)

User Ezzadeen
by
5.4k points